Chronic LD50 vs safest dose for the methanolic extract of curry leaves (Murraya koenigii) cultivated in Malaysia - Azzubaidi, Marwan Saad; Saxena, Anil Kumar; Alattraqchi, Ahmed Ghazi; Abdualkader, Abualrahman (Journal of Applied Pharmaceutical Science (http://www.japsonline.com), 2014)
Curry leaf viz. Murraya koenigiil eaves (MKL) is an ancient Ayurvedic medicinal plant that has recently been described as possessing robust anti-inflammatory and antioxidant activities. The current study was conducted to determine the long-term LD50 of the methanolic extract of MKL during daily oral administration. Five groups of Sprague Dawley rats were recruited into the study. Each group comprised of six rats including the control group (1). The oral MKL doses used for groups (2) to (5) were 50, 100, 200 and 400 mg/kg/day, respectively for a duration of ten weeks. The daily measured toxicity parameters were food and water consumption, body weight, general activity in forced swimming test and the cumulative mortalities. Group (5) showed 100% mortality within the first month of the study. Group (4) showed 50% mortality with signs of toxicity for the other 3 animals. Group (3) showed no mortalities but signs of toxicity for one animal were observed. No mortalities or toxicity signs were observed for any of group (2) animals. It can be concluded that the chronic LD50 for Malaysian cultivated MKL is 200 mg/kg/day, and the safest dose of MKL methanolic extract that can be implemented for long-term studies should not exceed 50 mg/kg/day.